Interdependence Practice among Elderly People with Severe Cataract Blindness in Malaysia - Abdul Mutalib, Othman; Nurulain, Mat Zin; Ahmad Shahir, Abdul Mutalib; Asma', Hassan (2017)
The Second Malaysian National Eye Survey in 2014 revealed the prevalence of blindness and low vision among the population aged 50 and above in the country as 1.2 % and 5.4 % respectively. The single main cause was cataract and the majority believed they did not need any surgical treatment. They seem to have limited awareness and failed to realize that individuals facing vision loss are at higher risk of falls, injuries, social isolation and depression, and the heightened effects of other health conditions. Interdependence is the practice of seeking support through reciprocal relationship and collaboration driven by intentions, activated by motivation and oriented by one’s cognition resulting in activities that determines the lifestyle and extent of physical and social activities. Thus, the aim of this study is to understand how the elderly people with severe cataract blindness in Malaysia could endure their progressive visual deterioration due to cataract by practicing interdependence. It will enable health practitioners to effectively advocate and promote earlier cataract surgical treatment to improve their vision and quality of life (QoL). The objective is to identify how they make sense and tolerate their progressive loss of vision by an in-depth exploration of their interdependence practice in actual life situation. It is a qualitative study employing interpretative phenomenological analysis (IPA) approach in health psychology. The participants consisted of 11 elderly people who are blind in both eyes due to cataract from the states of Terengganu, Pahang and Kelantan. Utilisation of IPA revealed a superordinate theme of ‘as long as they could ’ and 3 main themes namely issues regarding maintaining basic living needs, interpersonal cooperation, and moving about (mobility). This information provides better understanding on the barriers that is the reasons why these people had not gone for an earlier cataract surgery. It is pertinent to the various sectors that are directly or indirectly involved in the eyecare delivery system in Malaysia. Intensifying case detection and patients’ awareness on cataract by taking advantage of their interdependence practice is an effective way to improve wellbeing and QoL of the elderly people with cataract.